1984
DOI: 10.7326/0003-4819-100-3-393
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Metoclopramide Control of Cisplatin-Induced Emesis

Abstract: Using an original high-pressure liquid chromatographic assay, we measured serum levels of metoclopramide and defined a concentration-response relationship for metoclopramide control of cisplatin-induced emesis. Using a metoclopramide regimen of 2 mg/kg body weight intravenously every 2 hours for four doses, we found that serum levels greater than 850 ng/mL immediately before the third dose were associated with complete control of emesis (less than three episodes) in 78% of patients and partial control (three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 4 publications
2
28
0
Order By: Relevance
“…First, our subjects were younger with a median age of 41 years compared to 55 years in the trial of Kris and coworkers. Thus age may be an important factor as it has been shown that elderly patients are more sensitive to the antiemetic effects of metoclopramide (Meyer et al, 1984). Secondly, the differences in the two trial populations, study designs, chemotherapeutic regimens and criteria for evaluating response also provide additional explanations for the disparate re.sults.…”
Section: Resultsmentioning
confidence: 99%
“…First, our subjects were younger with a median age of 41 years compared to 55 years in the trial of Kris and coworkers. Thus age may be an important factor as it has been shown that elderly patients are more sensitive to the antiemetic effects of metoclopramide (Meyer et al, 1984). Secondly, the differences in the two trial populations, study designs, chemotherapeutic regimens and criteria for evaluating response also provide additional explanations for the disparate re.sults.…”
Section: Resultsmentioning
confidence: 99%
“…First, there is a metoclopramide dose concentration relationship to the metoclopramide serum levels regardless of the species or route of administration, and second, the rat, rabbit and dog eliminate metoclopramide from serum much faster than humans do (Bakke & Segura 1976;Bateman et al 1980Bateman et al , & 1983Brechot et al 1991;Citron et al 1987;Graffner et al 1979;Meyer et al 1984;Tam et al 1981;Tyson et al 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The log of the plasma drug concentration was stable from 2-9 h after administration suggesting that this preparation would be suitable for 8 or 12 hourly administration. However the delay in Cmax may result in delayed or complete absence of clinical effect since a rapid rise in CNS concentration may be important for therapeutic effect (Bateman et al, 1978(Bateman et al, , 1979 McGovern et al, 1983;Taylor & Bateman, 1983;Meyer et al, 1984). Much lower plasma drug concentrations 20 ng ml-' increase gastric emptying after intravenous administration (Bateman et al, 1978).…”
Section: Discussionmentioning
confidence: 99%